Low-smoke halogen-free material for cotton covered wire and preparation method of low-smoke halogen-free material

By using the synergistic role of hydroxide flame retardant, silicon ash powder, 3.5 zinc borate, and silica puppet coupling agent in the cable material, the problem of poor flame retardant effect of cable materials with high EVA resin content is solved , Achieve better flame retardant performance and meet the requirements of high -end products.

CN119350754APending Publication Date: 2025-01-24NANJING ZHONGCHAO NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693344.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When hydroxide is added to existing cable materials as halogen-free flame retardant, the flame retardant effect is poor for cable materials with high EVA resin content, and it is difficult to meet the requirements of high-end products.

Method used

The synergistic role of hydroxide flame retardant, silicon ash powder, 3.5 zinc borate, and silica tribal coupling agent, and add modifiers to the preferred solution to the preferred plan to improve the flame retardant performance Essence

Benefits of technology

In the case of adding a large amount of EVA resin, it significantly improves the flame retardant performance of low smoke and halogen -free with cloth wires, which can better meet the requirements of high -end products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cable materials, and particularly discloses a low-smoke halogen-free material for cotton covered wires and a preparation method of the low-smoke halogen-free material. A hydroxide flame retardant is selected as a halogen-free flame retardant, wollastonite powder and 3.5 hydrated zinc borate are added as flame retardant synergists, and a dispersing agent is limited to comprise a silane coupling agent. Through the synergistic effect of the hydroxide flame retardant, the wollastonite powder, the 3.5 hydrated zinc borate, the silane coupling agent and other components, the low-smoke halogen-free material for the cotton covered wire can obtain better flame retardant property under the condition that a large amount of EVA resin is added, and can better meet the requirements of high-end products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of cable materials, and more specifically, to a low-smoke halogen-free material for wiring cables and a preparation method thereof. Background Art

[0002] Fabricated wires are also called insulated wires. They are mainly composed of three parts: conductor, insulation layer and protective layer. They are suitable for various environments such as indoors and outdoors, exposed and concealed, and are generally used for power connections for lighting, power and other equipment. As global environmental awareness increases, the research and development and production of environmentally friendly and low-energy fabricated wire products will become an important development direction for the industry. In the future, the fabricated wire industry will maintain a steady growth trend, and technological innovation, expansion of application areas, green environmental protection and international development will become important directions for the development of the industry.

[0003] The insulation layer of the wiring harness is usually made of special cable materials. In order to prevent fire and reduce the damage of fire to the power system, flame retardants are generally added to the cable materials used to produce insulation materials. Traditional flame retardants are mainly halogen-containing flame retardants. The flame retardant mechanism of halogen-containing flame retardants is mainly achieved through the gas phase flame retardant effect of hydrogen halides, but hydrogen halides are highly toxic and can easily cause suffocation of people at the scene of a fire, and can also cause serious pollution to the environment during the incineration process. At present, high-end cable materials prefer to use halogen-free flame retardants, and the commonly used halogen-free flame retardants are mainly aluminum hydroxide and magnesium hydroxide.

[0004] With respect to the above-mentioned related technologies, the inventors believe that although adding hydroxide as a halogen-free flame retardant to cable materials can achieve a flame retardant effect, for cable materials with a high EVA resin content, due to the extremely easy combustion and droplet characteristics of EVA itself, the flame retardant effect of the halogen-free flame retardant is poor, and it is difficult to fully meet the requirements of high-end products. Summary of the invention

[0005] In the related art, although adding hydroxide as a halogen-free flame retardant can achieve a certain flame retardant effect, for cable materials with a high EVA resin content, the flame retardant effect is still poor and it is difficult to fully meet the requirements of high-end products. In order to improve this defect, the present application provides a low-smoke halogen-free material for wiring and a preparation method thereof.

[0006] In the first aspect, the present application provides a low-smoke halogen-free material for wiring, which adopts the following technical solution: A low-smoke halogen-free material for wiring cables comprises the following components in parts by weight: 28-32 parts of EVA resin, 9.5-10.5 parts of POE resin, 14-16 parts of LLDPE resin, 9.5-10.5 parts of compatibilizer, 1.5-2.5 parts of lubricant, 50-60 parts of halogen-free flame retardant, 21-25 parts of flame retardant synergist, 1.4-1.6 parts of masterbatch, 0.9-1.3 parts of dispersant, 0.4-0.6 parts of triallyl isocyanurate, and 0.6-1.0 parts of antioxidant; the halogen-free flame retardant comprises a hydroxide flame retardant, the flame retardant synergist comprises wollastonite powder and 3.5-water zinc borate, and the dispersant comprises a silane coupling agent.

[0007] By adopting the above technical scheme, the present application selects hydroxide flame retardant as halogen-free flame retardant, and adds wollastonite powder and 3.5 zinc borate water as flame retardant synergist. Wollastonite belongs to chain metasilicate, and is easy to dissociate. The fine particles in wollastonite powder are usually fibrous or needle-shaped. The silane coupling agent in the dispersant has a good binding effect with wollastonite powder, which can promote the uniform dispersion of wollastonite powder. Wollastonite powder can catalyze the formation of carbon layer during combustion, and can combine with the carbon layer to increase the density of the carbon layer. 3.5 zinc borate water can promote the gas phase flame retardant effect and condensed phase flame retardant effect of the system, and also promote the formation of carbon layer. Through the synergistic effect of components such as hydroxide flame retardant, wollastonite powder, 3.5 zinc borate water, silane coupling agent, etc., the low-smoke halogen-free material for wiring wire of the present application can achieve better flame retardant performance when a large amount of EVA resin is added, which can better meet the requirements of high-end products.

[0008] Preferably, the halogen-free flame retardant further comprises modified hydrotalcite, and the modified hydrotalcite is magnesium aluminum hydrotalcite with oxygen-containing acid anions intercalated between layers.

[0009] By adopting the above technical scheme, the present application defines the new component of the halogen-free flame retardant as modified hydrotalcite. The modified hydrotalcite can synergize with EVA to improve the dispersion effect of the hydroxide flame retardant, and the phosphate ions in the modified hydrotalcite can catalyze the degradation of EVA resin during combustion to form a carbon layer rich in POP and POC groups, which has a synergistic carbonizing effect with 3.5-hydrate zinc borate, hindering further combustion of the material, and helping to improve the flame retardant effect of low-smoke halogen-free materials for wiring wires.

[0010] Preferably, the oxygen-containing acid anion is a phosphate ion, and the modified hydrotalcite is prepared according to the following method: magnesium nitrate and aluminum nitrate are added to water to dissolve to obtain a salt solution, then the salt solution is added dropwise to water under nitrogen protection, sodium hydroxide is added for precipitation, after stirring and standing, the precipitate is filtered and recovered, the precipitate is added to a sodium phosphate solution for stirring and reaction, and then the precipitate is recovered and washed and dried to obtain the modified hydrotalcite.

[0011] By adopting the above technical solution, the present application firstly adopts the coprecipitation method to prepare the hydrotalcite precipitate, and then uses sodium phosphate for intercalation treatment to obtain the magnesium aluminum hydrotalcite with phosphate ions intercalated between the layers, that is, the modified hydrotalcite.

[0012] Preferably, the halogen-free flame retardant further comprises melamine cyanurate.

[0013] By adopting the above technical solution, melamine cyanurate can cooperate with modified hydrotalcite and 3.5 zinc borate to promote the carbonization of EVA resin. At the same time, melamine cyanurate can also absorb heat and cool down by sublimation when burning. In addition, melamine cyanurate will produce a large amount of non-flammable gas when decomposed by heat, and 3.5 zinc borate can make the gas phase flame retardant effect of melamine cyanurate more fully exerted. In summary, the addition of melamine cyanurate can effectively improve the flame retardant properties of low-smoke halogen-free materials for wiring.

[0014] Preferably, the wollastonite powder is pretreated as follows before use: The wollastonite powder is added into a container and heated in a water bath, and then a modifying agent is added and the wollastonite powder is stirred. After the stirring is completed, the wollastonite powder is dried to complete the pretreatment of the wollastonite; the modifying agent is silicone oil.

[0015] By adopting the above-mentioned technical scheme, the present application uses silicone oil as a modifying agent to carry out dry modification pretreatment of wollastonite powder, and obtains wollastonite powder with silicone oil molecules adsorbed on the surface. The silicone oil can improve the dispersion effect of the wollastonite powder, thereby helping to improve the flame retardant properties of low-smoke halogen-free materials for wiring harnesses.

[0016] Preferably, the amount of the modifying agent is 0.9-1.3% of the total weight of the wollastonite powder.

[0017] By adopting the above technical solution, the present application optimizes the dosage of the modifying agent, which helps to improve the flame retardant properties of the low-smoke halogen-free material for wiring harnesses.

[0018] Preferably, the dispersant comprises a silicone oil dispersant.

[0019] By adopting the above technical solution, the present application adds a silicone oil dispersant to the formula system. The silicone oil dispersant can further improve the dispersion effect of the pretreated wollastonite powder, which helps to improve the flame retardant properties of the low-smoke halogen-free material for wiring cables.

[0020] Preferably, in the method for pretreating the wollastonite powder, the water bath heating temperature is 70-80°C.

[0021] By adopting the above technical solution, the present application optimizes the water bath heating temperature in the pretreatment method, which helps to fully realize the modification of wollastonite powder and improve the flame retardant properties of low-smoke halogen-free materials for wiring.

[0022] Preferably, the modifying agent is amino silicone oil.

[0023] By adopting the above technical solution, amino silicone oil can form hydrogen bond adsorption with wollastonite powder, have a better modification effect on wollastonite powder, promote the uniform dispersion of wollastonite powder, and help to improve the flame retardant properties of low-smoke halogen-free materials for wiring harnesses.

[0024] In a second aspect, the present application provides a method for preparing a low-smoke halogen-free material for wiring harnesses, using the following technical solution.

[0025] A method for preparing a low-smoke halogen-free material for wiring, comprising the following steps: (1) EVA resin, POE resin, LLDPE resin, compatibilizer, lubricant, halogen-free flame retardant, flame retardant synergist, masterbatch, dispersant, triallyl isocyanurate, and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded through a single screw, and then air-cooled hot pelletized and cooled in a cyclone separator, and finally sieved using a vibrating screen to obtain a low-smoke, halogen-free material for wiring.

[0026] By adopting the above technical scheme, the method of the present application sequentially carries out batching, banburying, mixing, extrusion, pelletizing, cooling and screening, and finally obtains low-smoke halogen-free material for wiring.

[0027] In summary, this application has the following beneficial effects: 1. The present application selects hydroxide flame retardant as halogen-free flame retardant, adds wollastonite powder and 3.5% zinc borate as flame retardant synergist, and also limits the dispersant to include silane coupling agent. Through the synergistic effect of hydroxide flame retardant, wollastonite powder, 3.5% zinc borate, silane coupling agent and other components, the low-smoke halogen-free material for wiring wire of the present application can achieve better flame retardant performance when a large amount of EVA resin is added, which can better meet the requirements of high-end products.

[0028] 2. In the present application, modified hydrotalcite is preferably used as a component of the halogen-free flame retardant. The modified hydrotalcite can synergize with EVA to improve the dispersion effect of the hydroxide flame retardant. Moreover, the phosphate ions in the modified hydrotalcite can catalyze the degradation of the EVA resin during the combustion process to form a carbon layer rich in POP and POC groups, which has a synergistic carbonizing effect with 3.5-hydrate zinc borate, hindering the further combustion of the material, and helping to improve the flame retardant effect of the low-smoke halogen-free material for wiring wires.

[0029] 3. The present application also adds melamine cyanurate as a halogen-free flame retardant. Melamine cyanurate can cooperate with modified hydrotalcite and 3.5% zinc borate to promote the carbonization of EVA resin, and can also achieve heat absorption and cooling through sublimation. 3.5% zinc borate can make the gas phase flame retardant effect of melamine cyanurate more fully exerted. Therefore, the addition of melamine cyanurate can effectively improve the flame retardant properties of low-smoke halogen-free materials for wiring. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0031] Preparation example of modified hydrotalcite The following is an explanation using Preparation Example 1.

[0032] Preparation Example 1 In this preparation example, the modified hydrotalcite was prepared according to the following method: Add 0.15 mol magnesium nitrate and 0.05 mol aluminum nitrate into water and dissolve. Magnesium nitrate and aluminum nitrate are added to water in a molar ratio of 3:1 to dissolve to obtain a salt solution with a magnesium ion concentration of 1.5 mol / L, and then the salt solution is added dropwise to an equal volume of water under nitrogen protection, sodium hydroxide is added to adjust the pH to 8.5, and the mixture is stirred evenly and allowed to stand at 70°C for 12 hours, and then the precipitate is filtered and recovered, and 100 mL of a 30 wt% sodium phosphate solution is added to 1 g of the precipitate, and the precipitate is added to the sodium phosphate solution and stirred for reaction for 24 hours, and then the precipitate is recovered and washed and dried to obtain a modified hydrotalcite. Example

[0033] Examples 1-5 The following description is given by taking Example 1 as an example.

[0034] Example 1 In this embodiment, the model of EVA resin is Formosa Plastics 7470, the model of POE resin is Dow 8200, the model of LLDPE resin is 7042, the model of compatibilizer is Energy Light M2, the lubricant is silicone masterbatch, the halogen-free flame retardant is hydroxide flame retardant, the hydroxide flame retardant is composed of aluminum hydroxide and magnesium hydroxide mixed in a weight ratio of 6:5, the flame retardant synergist is composed of wollastonite powder and 3.5 water zinc borate mixed in a weight ratio of 20:3, the masterbatch is 3028 masterbatch, the dispersant is silane coupling agent (KH172), and the antioxidant is composed of antioxidant 1010 and antioxidant 1024 mixed in a weight ratio of 5:3.

[0035] This embodiment provides a low-smoke halogen-free material for wiring, including the following components: 28 kg of EVA resin, 9.5 kg of POE resin, 14 kg of LLDPE resin, 9.5 kg of compatibilizer, 1.5 kg of lubricant, 50 kg of halogen-free flame retardant, 21 kg of flame retardant synergist, 1.4 kg of masterbatch, 0.9 kg of dispersant, 0.4 kg of triallyl isocyanurate, and 0.6 kg of antioxidant; This embodiment also provides a method for preparing a low-smoke halogen-free material for wiring, comprising the following steps: (1) EVA resin, POE resin, LLDPE resin, compatibilizer, lubricant, halogen-free flame retardant, flame retardant synergist, masterbatch, dispersant, triallyl isocyanurate, and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded through a single screw, and then air-cooled hot pelletized and cooled in a cyclone separator, and finally sieved using a vibrating screen to obtain a low-smoke, halogen-free material for wiring.

[0036] As shown in Table 1, the main difference between Examples 1-5 is that the raw material ratios of the low-smoke halogen-free material used for wiring wiring are different.

[0037] Table 1 Raw material ratio of low smoke zero halogen materials for wiring sample Example 1 Example 2 Example 3 Example 4 Example 5 EVA resin / kg 28 29 30 31 32 POE resin / kg 9.5 9.8 10.0 10.2 10.5 LLDPE resin / kg 14 14.5 15 15.5 16 Compatibilizer / kg 9.5 9.8 10.0 10.2 10.5 Lubricant / kg 1.5 1.8 2.0 2.2 2.5 Halogen-free flame retardant / kg 50 53 55 57 60 Flame retardant synergist / kg 21 22 23 24 25 Masterbatch / kg 1.4 1.45 1.5 1.55 1.6 Dispersant / kg 0.9 1.0 1.1 1.2 1.3 Triallyl isocyanurate / kg 0.4 0.45 0.5 0.55 0.6 Antioxidant / kg 0.6 0.7 0.8 0.9 1.0 Example 6 The difference between this embodiment and embodiment 5 is that the halogen-free flame retardant is prepared by mixing a hydroxide flame retardant and modified hydrotalcite in a weight ratio of 5:1, and the modified hydrotalcite is prepared according to the method of preparation example 1.

[0038] Example 7 The difference between this embodiment and embodiment 6 is that the halogen-free flame retardant is prepared by mixing a hydroxide flame retardant, modified hydrotalcite and melamine cyanurate in a weight ratio of 5:1:0.2.

[0039] Example 8 The difference between this embodiment and embodiment 7 is that the wollastonite powder is pretreated according to the following method before use: Add wollastonite powder into a container, heat it in a water bath at 65°C, then add the modifying agent, stir the wollastonite powder, and dry it 30 minutes after stirring to complete the pretreatment of the wollastonite.

[0040] In this embodiment, the modifying agent is silicone oil, the type of silicone oil is dimethyl silicone oil (CAS: 63148-62-9), and the amount of silicone oil is 0.6% of the total weight of wollastonite powder. When used, the silicone oil is added to petroleum ether to prepare a diluent with a concentration of 20wt%, and then added to the wollastonite powder.

[0041] Example 9 The difference between this embodiment and embodiment 8 is that the amount of silicone oil used is 0.9% of the total weight of wollastonite powder.

[0042] Example 10 The difference between this embodiment and embodiment 8 is that the amount of silicone oil used is 1.1% of the total weight of wollastonite powder.

[0043] Embodiment 11 The difference between this embodiment and embodiment 8 is that the amount of silicone oil used is 1.3% of the total weight of wollastonite powder.

[0044] Example 12 The difference between this embodiment and embodiment 11 is that the dispersant is formed by mixing a silane coupling agent and a silicone oil dispersant in a weight ratio of 2:1, and the silicone oil dispersant is dimethyl silicone oil (CAS: 63148-62-9).

[0045] Example 13 The difference between this embodiment and embodiment 12 is that in the method of pretreating wollastonite powder, the water bath heating temperature is 70°C. Embodiment 14 The difference between this embodiment and embodiment 12 is that in the method of pretreating wollastonite powder, the water bath heating temperature is 75°C.

[0046] Embodiment 15 The difference between this embodiment and embodiment 12 is that in the method of pretreating wollastonite powder, the water bath heating temperature is 80°C.

[0047] Example 16 The difference between this embodiment and embodiment 15 is that amino silicone oil (CAS: 63148-62-0) is used as the modifying agent.

[0048] Embodiment 17 The difference between this embodiment and embodiment 6 is that in the method for preparing modified hydrotalcite, the sodium phosphate solution is replaced by deionized water.

[0049] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the flame retardant synergist does not include wollastonite powder.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is that the flame retardant synergist does not include 3.5-hydrate zinc borate.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the raw material components of the low-smoke halogen-free material for wiring wiring do not include a dispersant.

[0052] Performance testing methods The material to be tested was made into a sample using a flat vulcanizer at 5 MPa and 120° C., and then irradiated and cross-linked at an absorbed dose of 180 kGy to obtain a sample to be tested for later use.

[0053] With reference to the provisions of GB / T 32129-2015 Halogen-free and low-smoke flame-retardant cable materials for wires and cables, the oxygen index of the test samples was tested. The results are shown in Table 2.

[0054] Table 2 Oxygen index test results sample Oxygen index / % sample Oxygen index / % Example 1 33.7 Embodiment 11 36.5 Example 2 33.8 Example 12 36.8 Example 3 34.1 Example 13 37.2 Example 4 34.0 Embodiment 14 37.2 Example 5 34.2 Embodiment 15 37.3 Example 6 34.9 Example 16 37.7 Example 7 35.8 Embodiment 17 34.3 Example 8 36.0 Comparative Example 1 29.1 Example 9 36.2 Comparative Example 2 29.6 Example 10 36.3 Comparative Example 3 28.4 Combining Examples 1-5 and Comparative Examples 1-2 and Table 2, it can be seen that the oxygen index measured in Examples 1-5 is higher than that in Comparative Examples 1-2, indicating that the present application fully improves the flame retardant properties of the material by the synergistic effect of components such as hydroxide flame retardant, wollastonite powder, 3.5 water zinc borate, and silane coupling agent while adding more EVA resin, and the obtained low-smoke halogen-free material for wiring can better meet the requirements of high-end products.

[0055] Combining Example 1 and Comparative Example 3 with Table 2, it can be seen that the oxygen index measured in Example 1 is higher than that in Comparative Example 3. This is because in Comparative Example 3, in the absence of a dispersant, the flame retardant and the flame retardant synergist are not fully dispersed, thereby affecting the flame retardant properties of the material.

[0056] Combining Example 5 and Example 6 with Table 2, it can be seen that the oxygen index measured in Example 6 is higher than that in Example 5. This is because the modified hydrotalcite can synergistically improve the dispersion effect of the hydroxide flame retardant with EVA, and the phosphate ions in the modified hydrotalcite can catalyze the degradation of the EVA resin during the combustion process to form a carbon layer rich in POP and POC groups, which has a synergistic carbonization effect with 3.5-hydrate zinc borate, hindering further combustion of the material, and helping to improve the flame retardant effect of the low-smoke halogen-free material for wiring wires.

[0057] Combining Example 6 and Example 7 and Table 2, it can be seen that the oxygen index measured in Example 7 is higher than that in Example 6. This is because melamine cyanurate can synergistically promote the carbonization of EVA resin with modified hydrotalcite and 3.5-water zinc borate. At the same time, melamine cyanurate can also absorb heat and cool down by sublimation during combustion, and 3.5-water zinc borate can also make the gas phase flame retardant effect of melamine cyanurate more fully exerted, thereby effectively improving the flame retardant properties of low-smoke halogen-free materials for wiring.

[0058] Combining Example 7, Example 8-11 and Table 2, it can be seen that the oxygen index measured in Example 8-11 is higher than that in Example 7. This is because the wollastonite powder after silicone oil pretreatment has a better dispersion effect, which helps to improve the flame retardant properties of the low-smoke halogen-free material for wiring. Combining Examples 9-11, it can be seen that when the amount of the modifying agent is 0.9-1.3% of the total weight of the wollastonite powder, the flame retardant properties of the low-smoke halogen-free material for wiring are better.

[0059] Combining Example 11, Example 12 and Table 2, it can be seen that the oxygen index measured in Example 12 is higher than that in Example 11. This is because Example 12 uses silicone oil as a dispersant, and the silicone oil dispersant can further improve the dispersion effect of the pretreated wollastonite powder, thereby helping to improve the flame retardant properties of the low-smoke halogen-free material for wiring.

[0060] Combining Example 12, Examples 13-15 and Table 2, it can be seen that the oxygen index measured in Examples 13-15 is higher than that in Example 12, indicating that in the method of pre-treating wollastonite powder, setting the water bath heating temperature to 70-80°C is more conducive to fully realizing the modification treatment of wollastonite powder, improving the dispersion effect of wollastonite powder, and improving the flame retardant performance of low-smoke halogen-free material for wiring. Combining Example 15 and Example 16 with Table 2, it can be seen that the oxygen index measured in Example 16 is higher than that in Example 15. This is because the amino silicone oil can form hydrogen bond adsorption with wollastonite powder, has a better modification effect on the wollastonite powder, promotes the uniform dispersion of the wollastonite powder, and helps to improve the flame retardant properties of the low-smoke halogen-free material for wiring.

[0061] It can be seen from Example 6 and Example 17 and Table 2 that the oxygen index measured in Example 6 is higher than that in Example 17. This is because in the absence of phosphate ions, Example 17 adds magnesium-aluminum hydrotalcite that has not been intercalated, which makes it difficult to achieve the effect of promoting the degradation of EVA resin, affecting the synergistic carbonization effect between the components, resulting in poor flame retardant properties of the material.

[0062] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A low-smoke, halogen-free material for wiring, characterized in that: The invention comprises the following components in parts by weight: 28-32 parts of EVA resin, 9.5-10.5 parts of POE resin, 14-16 parts of LLDPE resin, 9.5-10.5 parts of compatibilizer, 1.5-2.5 parts of lubricant, 50-60 parts of halogen-free flame retardant, 21-25 parts of flame retardant synergist, 1.4-1.6 parts of masterbatch, 0.9-1.3 parts of dispersant, 0.4-0.6 parts of triallyl isocyanurate and 0.6-1.0 parts of antioxidant; the halogen-free flame retardant comprises a hydroxide flame retardant, the flame retardant synergist comprises wollastonite powder and 3.5-water zinc borate, and the dispersant comprises a silane coupling agent.

2. The low-smoke zero-halogen material for wiring cables according to claim 1, characterized in that: The halogen-free flame retardant further comprises modified hydrotalcite, and the modified hydrotalcite is magnesium aluminum hydrotalcite with oxygen-containing acid anions intercalated between layers.

3. The low-smoke zero-halogen material for wiring cables according to claim 2, characterized in that: The oxygen-containing acid anion is a phosphate ion, and the modified hydrotalcite is prepared according to the following method: Magnesium nitrate and aluminum nitrate are added into water to dissolve to obtain a salt solution, then the salt solution is added dropwise into water under nitrogen protection, sodium hydroxide is added for precipitation, the precipitate is filtered and recovered after stirring and standing, the precipitate is added into a sodium phosphate solution for stirring reaction, then the precipitate is recovered and washed and dried to obtain a modified hydrotalcite.

4. The low-smoke zero-halogen material for wiring cables according to claim 3, characterized in that: The halogen-free flame retardant further comprises melamine cyanurate.

5. The low-smoke zero-halogen material for wiring cables according to claim 1, characterized in that: The wollastonite powder is pretreated as follows before use: The wollastonite powder is added into a container and heated in a water bath, and then a modifying agent is added and the wollastonite powder is stirred. After the stirring is completed, the wollastonite powder is dried to complete the pretreatment of the wollastonite; the modifying agent is silicone oil.

6. The low-smoke zero-halogen material for wiring cables according to claim 5, characterized in that: The dosage of the modifying agent is 0.9-1.3% of the total weight of the wollastonite powder.

7. The low-smoke zero-halogen material for wiring cables according to claim 6, characterized in that: The dispersant includes a silicone oil dispersant.

8. The low-smoke zero-halogen material for wiring cables according to claim 5, characterized in that: In the method for pretreating the wollastonite powder, the temperature of the water bath heating is 70-80°C.

9. The low-smoke zero-halogen material for wiring cables according to claim 5, characterized in that: The modifying agent is amino silicone oil.

10. The method for preparing the low-smoke zero-halogen material for wiring wire according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) EVA resin, POE resin, LLDPE resin, compatibilizer, lubricant, halogen-free flame retardant, flame retardant synergist, masterbatch, dispersant, triallyl isocyanurate and antioxidant are mixed and added into an internal mixer for internal mixing; (2) The material is fed into a twin-screw extruder through a conical feeder for mixing, and then extruded by a single screw, and then air-cooled hot pelletized and cooled by a cyclone separator, and finally sieved using a vibrating screen to obtain low-smoke halogen-free material for wiring.